Design and Characteristics of Underwater Stacked Capacitive Power Transfer Coupler and Analysis of Propagation in Water Medium - Kyeungwon Bang; Sangwook Park (Applied Sciences)
This study provides a theoretical analysis of how the electrical characteristics of the medium affect the propagation of electric fields. Every medium has specific electrical conductivity and permittivity values and can be evaluated as a good conductor or a good dielectric depending on the ratio of conduction current to displacement current. The strength of the electric field decreases significantly with the propagation distance due to the influence of high conductivity. In conclusion, even media with a high permittivity may be unsuitable for improving the performance of the capacitive power transfer (CPT) system depending on its conductivity. The analysis was verified for four types of water with different conductivities. In addition, we designed a stacked CPT coupler structure and analyzed its underwater transfer characteristics. In conclusion, unlike the parallel CPT coupler, the stacked CPT coupler is relatively disadvantageous for underwater use.